The probiotics influence on the acute osmo-secretory diarrhea in children - E. Dondurey; I. Kosenko; E. Kostitsyna; Y. Polkovnikova; A. Shestakova (LLC "Diagnostics and Vaccines", 2023)
Nowadays acute gastroenteritis retains the leading infectious disorder in children, has viral etiology and osmosecretory type of diarrhea in the most cases. Probiotics are considered highly effective medicines as part of the complex gastroenteritis therapy in children. The choice of the probiotics is limited by strains with proven efficacy and complicated by a large range of commercially available probiotics. The aim of the comparative post-registration prospective study was to evaluate the efficacy and safety the probiotic drug Adiarin Probio for treatment of osmosecretory diarrhea inpatient children. The study included 60 hospitalized children aged 6 months to 7 years. Results: the efficacy and safety as well as high adherence to the Adiarin Probio in children with osmosecretory diarrhea were confirmed.